Implementasi Algoritma CT-PRO Untuk Menentukan Pola Frekuensi Judul Skripsi Teknik Informatika Universitas Harapan Medan - Muchriza Akbar Bancin; Herlina Harahap; Rismayanti (Universitas Harapan Medan, 2021)
The thesis is a term used to describe a scientific book in the form of an explanation of the results studied. In this study there was a problem that every time a student made a thesis title was difficult for students to decide which topic to be discussed. So that the study program was also somewhat overwhelmed to provide input on what title would be appointed for the thesis. With the help of data mining the CT-Pro algorithm is expected to help the study program in determining the frequency pattern of the title of the thesis submitted by students. So that the study program can see students more likely to submit the title of the thesis in which direction, whether it is in accordance with the science they control or not. This research produces a media network in determining specialization in taking thesis titles.